RESIDENT PROGENITOR CARDIAC CELLS IN PATIENTS WITH DILATED CARDIOMYOPATHY AND CONGESTIVE HEART FAILURE - T. G. Kulikova; O. V. Stepanova; M. P. Valihov; A. Yu. Shhedrina; A. N. Samko; V. P. Masenko; S. N. Tereshhenko (Рациональная фармакотерапия в кардиологии)
Aim. To study content of resident progenitor cardiomyocytes in endomyocardial biopsy samples of patients with dilated cardiomyopathy (DCM) and heart failure (HF) at different disease stages and relate it to patient clinical characteristics.Material and methods. Resident progenitor cardiomyocytes were studied in endomyocardial biopsy samples from 14 patients (age from 26 to 52 years old) with DCM and HF by immunofluorescence method. Results were analyzed individually for each patient.Results. Resident progenitor cardiomyocytes expressing simultaneously stem cell markers c-kit, MDR-1 and early cardiomyocyte differentiation markers GATA-4 and Nkx2.5 were found in endomyocardial biopsy samples from patients with DCM and HF. Resident progenitor cardiomyocytes detected by these cell markers were found in all patients at all disease stages.Conclusion. Results show that the myocardial regenerative processes exist at all stages of the disease progression.